Fundamentals of Entrepreneurship ENT300 Wirama Bakery / Aimi Suhaila Saharuddin… [et al.] - Saharuddin, Aimi Suhaila; Jamzain, Syazwani; Abg. Bunsu, Abg. Norhickman; Ejau, Ruth Lua; Mahidin, Nur Iman; Awgku Arni, Awgku Mohd. Nazrin (2010)
Wirama Bakery is a company that provides bakery to the customers in Sarawak. This company provides to sell the bakery and also accepts booking or order from customer to do the ceremony such as dinner, wedding function, and many more. Additionally, this company will supply out of the town of the product produced. This business premise is for both administrative building and manufacturing or producing various types of cakes and buns.